The Effect of Reciprocal Teaching on Social Science Elementary Problem Solving Skills - Diyas Age Larasati (Universitas of Muhammadiyah Makassar, 2020)
Abstract. The purpose of this study was to determine the effect of reciprocal teaching on IPS elementary problem solving skills. This research method was quasi-experimental using two randomized control group pretest-posttest design. Two classes were chosen, namely the experimental class by applying the reciprocal teaching approach and the control class using the lecture and discussion approach. The population of this research is class IV SDN Pakis V Surabaya, with sample class IV-A as the experimental class and class IV-B as the control class. Each class has 35 students. The instruments of this study used tests of problem solving abilities, observation sheets, and documentation. Essay-type problem ability tests with 5-item questions. Before being tested in research, the problem is firstly tested based on the level of validity, level of difficulty, different power, and reliability. The analysis technique in this study uses the t test formula with the help of SPSS 25.0 for window. Significant level α = 95%. H0 is accepted if t arithmetic t table, and H0 is rejected if t arithmetic t table. And H1 is accepted if the significant value 0.05 and t arithmetic t table. The results of the analysis of research data through the t test, showed a significant number of 0.01. This shows that H0 is rejected and H1 is accepted because significant values of 0.01 0.05 and 12.705 t table 1.697. The results of the analysis indicate that there is an effect of reciprocal teaching on the ability to solve social studies in elementary school.Keywords: Reciprocal Teaching, Problem Solving Ability, IPSAbstrak. Tujuan penelitian ini untuk mengetahui pengaruh reciprocal teaching terhadap kemampuan pemecahan masalah IPS SD. Metode penelitian ini kuasi eksperimen dengan menggunakan two randomized control group pretes-posttest design. Dipilih secara acara dua kelas, yaitu kelas eksperimen dengan menerapkan pendekatan reciprocal teaching dan kelas kontrol dengan menggunakan pendekatan ceramah dan diskusi. Populasi penelitian ini kelas IV SDN Pakis V Surabaya, dengan sampel Kelas IV-A sebagai kelas eksperimen dan kelas IV-B sebagai kelas kontrol. Masing-masing kelas berjumlah 35 siswa. Intrumen penelitian ini menggunakan tes kemampuan pemecahan masalah, lembar observasi, dan dokumentasi. Tes kemampuan masalah berjenis esai dengan 5butir soal. Sebelum diujikan dalam penelitian, terlebih dahulu soal tersebut diuji berdasarkan tingkat validitas, tingkat kesukaran, daya beda, dan reliabilitas. Teknik analisis dalam penelitian ini menggunakan rumus uji t dengan bantuan SPSS 25.0 for window. Tingkat signifikan α= 95%. H0 diterima apabila t hitung t tabel, dan H0 ditolak apabila t hitung t tabel. Dan H1 diterima apabila nilai siginifikan 0,05 dan t hitung t table. Hasil analisis data penelitian melalui uji t, menunjukkan angka signifikan sebesar 0,01. Hal tersebut menunjukkan bahwa H0 ditolak dan H1 diterima karena nilai signifikan 0,01 0,05 dan 12,705 t tabel 1,697. Hasil analisis tersebut menunjukkanKata Kunci: Reciprocal Teaching, Kemampuan Pemecahan Masalah, IPS